2021
DOI: 10.2217/fon-2021-1109
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Adverse Events and Costs of Nivolumab Plus Ipilimumab Versus Sunitinib in Advanced Renal Cell Carcinoma

Abstract: Aims: To assess grade 3/4 adverse events (AEs) and costs of first-line nivolumab plus ipilimumab (NIVO + IPI) versus sunitinib in advanced or metastatic renal cell carcinoma. Methods: Individual patient data from the all treated population in the CheckMate 214 trial (NIVO + IPI, n = 547; sunitinib, n = 535) were used to calculate the number of AEs. AE unit costs were obtained from US 2017 Healthcare Cost and Utilization Project and inflated to 2020 values. Results: The proportion of patients experiencing grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The following costeffectiveness analysis was identified to inform the topic. 149,150 Comparisons of Nivo plus Ipi versus sunitinib and Nivo plus Ipi versus axitinib plus pembrolizumab versus sunitinib both found Nivo plus Ipi to be the most cost-effective combination in treating mRCC. 151,152 However, in the absence of widely agreed upon definitions for incremental cost-effectiveness ratios and willingness to pay thresholds per quality-adjusted life-years gained, these analyses are limited.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…The following costeffectiveness analysis was identified to inform the topic. 149,150 Comparisons of Nivo plus Ipi versus sunitinib and Nivo plus Ipi versus axitinib plus pembrolizumab versus sunitinib both found Nivo plus Ipi to be the most cost-effective combination in treating mRCC. 151,152 However, in the absence of widely agreed upon definitions for incremental cost-effectiveness ratios and willingness to pay thresholds per quality-adjusted life-years gained, these analyses are limited.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…Over 18 months, the cumulative all-cause and treatment-related grade 3/4 AE costs were $3428 and $3524 less per patient, respectively, for those treated with nivolumab plus cabozantinib compared to sunitinib. In addition, a similar analysis found that patients who received nivolumab plus ipilimumab also had lower average per-patient all-cause grade at 12 months ($15,170 vs. $20,342) compared to sunitinib [ 26 ]. Together, these results highlight the value of nivolumab-based combination therapies for the first-line treatment of aRCC compared to the current standard of care in the US.…”
Section: Discussionmentioning
confidence: 99%
“…The highest AE costs occurred at month 2 for the nivolumab plus cabozantinib arm and at month 1 for the sunitinib arm. Similarly, in CheckMate 214, the highest AE costs occurred at month 3 for nivolumab plus ipilimumab and at month 1 for sunitinib [ 26 ]. Similar onset times of AEs were also reported for other targeted aRCC therapies, such as sorafenib, and other studies of sunitinib, in which most treatment-related AEs developed shortly within the first treatment cycle (6 weeks) and decreased with each subsequent cycle [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the data from CheckMate 214 in conjunction with the U.S. 2017 Healthcare Cost and Utilization Project, investigators performed a cost analysis using temporal trends and costs related to grade ≥ 3 TRAE. Treatment with ipilimumab/nivolumab was associated with lower grade ≥ 3 TRAE costs than sunitinib [ 50 ]. Ongoing studies will help us better explore the financial toxicity associated with newer therapies, but cost considerations are complex and vary tremendously on a patient-to-patient basis based on insurance coverage or lack thereof.…”
Section: Factors To Consider With Front-line Therapy Optionsmentioning
confidence: 99%